Matrix Metalloproteinases and Blood-Brain Barrier Disruption in Acute Ischemic Stroke - Lakhan, Shaheen E.; Kirchgessner, Annette; Tepper, Deborah; Aidan, Leonard (Frontiers in Neurology, 2013)
Ischemic stroke continues to be one of the most challenging diseases in translational neurology. Tissue-type plasminogen activator (tPA) remains the only approved treatment for acute ischemic stroke, but its use is limited to the first hours after stroke onset due to an increased risk of hemorrhagic transformation over time resulting in enhanced brain injury. In this review we discuss the role of matrix metalloproteinases (MMPs) in blood-brain barrier (BBB) disruption as a consequence of ischemic stroke. MMP-9 in particular appears to play an important role in tPAassociated hemorrhagic complications. Reactive oxygen species (ROS) can enhance the effects of tPA on MMP activation through the loss of caveolin-1, a protein encoded in the cav-1 gene that serves as a critical determinant of BBB permeability. This review provides an overview of MMPs' role in BBB breakdown during acute ischemic stroke. The possible role of MMPs in combination treatment of acute ischemic stroke is also examined.